2008
DOI: 10.1007/s00464-008-9935-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laparoscopic mesenteric/retroperitoneal lymph node biopsy

Abstract: Laparoscopic lymph node biopsy is a safe effective alternative to open surgical biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…However, in some occasions the anatomic location of the lymph node as well as undesirable events such as bleeding from the biopsy site may necessitate conversion of the procedure to open. In the present cohort we were able to achieve a zero conversion rate but according to the literature the latter could be high enough reaching 17-20% [9,10,19]. Careful interpretation of the preoperative CT scans as well as the standardization of the technique are vital steps for avoiding conversions.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, in some occasions the anatomic location of the lymph node as well as undesirable events such as bleeding from the biopsy site may necessitate conversion of the procedure to open. In the present cohort we were able to achieve a zero conversion rate but according to the literature the latter could be high enough reaching 17-20% [9,10,19]. Careful interpretation of the preoperative CT scans as well as the standardization of the technique are vital steps for avoiding conversions.…”
Section: Discussionmentioning
confidence: 50%
“…However, the latter is an invasive procedure which is associated with a prolonged convalescence and a delay in the final treatment. Lately, laparoscopy has been increasingly applied for the biopsy of abdominal lymph nodes [9,10]. The profound advantages of this approach are the excellent diagnostic accuracy, the minimal surgical trauma and the fast recovery [10].…”
Section: Introductionmentioning
confidence: 99%
“…Diulus et al [10] reported a conversion rate of 13 %, but a low complication Fig. 1 A retroperitoneal tumor was located between the right internal and external iliac arteries near the ureter (case 6).…”
Section: Discussionmentioning
confidence: 96%
“…In most previous reports, the procedure was performed by general surgeons using the transperitoneal approach [411121314]. However, a relatively high rate of conversion to laparotomy has been described, usually because of inadequate exposure, insufficient tissue, or postoperative adhesions.…”
Section: Introductionmentioning
confidence: 99%